Pengaruh Pembangunan Lokasi Kuliner Jombang Terhadap Kinerja Jalan Kh.A.Dahlan Dan Jalan Gubernur Suryo - M. Afiif Zuhdi Athaullah; Iwan Cahyono; Saiful Arfaah (GLOBAL SCIENTS PUBLISHER, 2025)
Urban growth often leads to increased traffic, especially in economic and social hubs. In Jombang Regency, Jalan KH. Ahmad Dahlan and Jalan Gubernur Suryo are two busy roads affected by the 2024 development of “Kuliner Jombang,” located between them, with the former serving as the main entrance and the latter as the exit. This study, based on the Indonesian Road Capacity Manual (PKJI 2023), examines traffic volume, degree of saturation, and road performance before and after the development. Field surveys recorded peak volumes of 6,027 veh/hour on Jalan KH. Ahmad Dahlan and 4,116 veh/hour on Jalan Gubernur Suryo. Saturation levels rose from 0.59 to 0.95 and 0.61 to 0.98, respectively. The results show a significant impact, with a 62% increase on Jalan KH. Ahmad Dahlan and 61% on Jalan Gubernur Suryo, indicating reduced road performance and potential congestion growth in the future.